Games to foster mathematical thinking in children from four to eight years old (Edma 0-6: Educación Matemática en la Infancia, 2021)
Playing is an essential activity for the physical, psychological, social and cognitive development of the child and its use as a resource or activity in the classroom is important, not only in the years of Early Childhood Education, but also, in the Primary Education stage. In this article we analyze three commercial games (Tiny Polka Dot, Shut the box and The genius square) as a possible resource to foster the development of mathematical thinking in children between four and eight years old. The learning of mathematics is made of analysis, patterns, connections, explorations, strategies, trying paths, persevering, thinking, accounting for your actions, explaining, asking questions... and due to these same elements, games can help to learn to think mathematically.
Keywords: Play and mathematics; Mathematics education; Early Childhood Education; Didactics of mathematics; Problem solving; Mathematical thinking